Analysis of building planning over cable stayed bridge: The simulation - Resinta, Tria; Rifai, Andri Irfan; Umar, Usmanul Hayadi; Isradi, Muhammad (International Journal Labs, 2024)
Cable-stayed bridges with box girders are essential innovations in civil engineering, especially for long-span structures. These bridges, reinforced with prestressed cables and box girders, are designed to handle significant loads but remain vulnerable to aerodynamic forces, particularly wind. The vulnerability is measured using the Pb parameter, as defined by the Ministry of Public Works (2015), which helps determine the windbreak structures needed for stability. This study analyzes the aerodynamic stability of bridge decks with widths of 8 m, 13 m, and 19 m on a 420 m bridge, featuring a 220 m main span and two 100 m side spans. The results reveal that the larger the deck width-to-span ratio, the higher the structure's natural frequency, which improves stability. The natural frequency values were recorded at 0.3 Hz for a 7 m deck (3.2%), 0.43 Hz for a 12 m deck (5.48%), and 0.53 Hz for an 18 m deck (8.2%). The most stable span ratio was found with the 18 m deck, with a Pb value of 0.04, showing minimal wind load effects. Moreover, a larger deck width enhances aerodynamic stability and extends the bridge’s service life by reducing damage risk from wind loads.